Small and Medium Enterprise Research in Supply Chain Management: The Case for Single‐Respondent Research Designs. Issue 1 (18th December 2017) - Kull, Thomas J.; Kotlar, Josip; Spring, Martin
Abstract : Deciding on the number of respondents in a data‐collection instrument is a key design consideration requiring supply chain researchers to balance multiple competing factors. The debate on this respondent design question may unintentionally disregard over 95% of enterprises engaged in supply chains: small and medium enterprises (SMEs). We present arguments for why single‐respondent designs can be more appropriate in the SME setting, particularly when considering the various facets of supply chain management and the untapped potential of SCM‐SME research. Assuring that SCM theoretical frameworks and research designs allow for SME inclusion will be important in aiding the SCM field to progress forward.